2010
DOI: 10.4049/jimmunol.1001617
|View full text |Cite
|
Sign up to set email alerts
|

Domain Swapping Reveals Complement Control Protein Modules Critical for Imparting Cofactor and Decay-Accelerating Activities in Vaccinia Virus Complement Control Protein

Abstract: Vaccinia virus encodes a structural and functional homolog of human complement regulators named vaccinia virus complement control protein (VCP). This four-complement control protein domain containing secretory protein is known to inhibit complement activation by supporting the factor I-mediated inactivation of complement proteins, proteolytically cleaved form of C3 (C3b) and proteolytically cleaved form of C4 (C4b) (termed cofactor activity), and by accelerating the irreversible decay of the classical and to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 66 publications
3
11
0
Order By: Relevance
“…Our results provided here clearly point out that CCP2 and CCP3 of Kaposica are most vital for its CFA, because swapping of these with the homologous domains of DAF results in complete loss of the CFA. These data also gain support from our earlier studies with viral RCAs Kaposica and VCP (16,17). Furthermore, by swapping the intercysteine segments and by site-directed mutagenesis, we also identify the intercysteine regions and residues in CCP2 and CCP3 of Kaposica critical for its CFA.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our results provided here clearly point out that CCP2 and CCP3 of Kaposica are most vital for its CFA, because swapping of these with the homologous domains of DAF results in complete loss of the CFA. These data also gain support from our earlier studies with viral RCAs Kaposica and VCP (16,17). Furthermore, by swapping the intercysteine segments and by site-directed mutagenesis, we also identify the intercysteine regions and residues in CCP2 and CCP3 of Kaposica critical for its CFA.…”
Section: Discussionsupporting
confidence: 84%
“…There is, however, a caveat-swapping strategy, although superior than domain deletions, may lead to structural alteration because of disruption of the interaction between modules. Having said the above, we would like to point out that this strategy did prove successful in identifying the functional modules in another viral RCA: vaccinia virus complement control protein (VCP) (17). We, thus, swapped each of the Kaposica modules with the homologous modules of human DAF, which is also composed of four CCP modules but lacks CFA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of the mechanisms of interaction of VCP with its target proteins showed that it follows a simple 1:1 binding model, with very fast on-and-off rates [ Attempts to identify the functional domains suggested that different domains contribute to different functional activities, but that all four modules contribute to its optimal activity [91]. Our very recent data indicate that domains 2 and 3 in VCP provide the binding surface for factor I, while domain 1 mediates the dissociation of the protease subunit from the classical and AP C3 convertases, respectively [100]. Owing to its inhibitory nature, the molecule has also been evaluated for its effectiveness in several disease conditions (reviewed in [101,102]).…”
Section: Poxviral Rca Homologsmentioning
confidence: 96%
“…VCP is a homolog of the human regulators of complement activation proteins and has been shown to inhibit antibody-mediated complement-enhanced neutralization of vaccinia virus in vitro (10). Mechanistically, VCP functions to facilitate viral pathogenesis by inhibiting complement activation (11,12) through enhancement of factor I-mediated inactivation of complement proteins C3b (13) and C4b and by accelerating the dissociation of the C3 convertase of the complement pathway (14,15). The C3L gene is conserved among vaccinia virus strains, and homologs of C3L encoding inhibitors of complement enzymes (ICEs) have been described in other orthopoxviruses, including variola virus (VARV), monkeypox virus (MPXV), cowpox virus (CPXV), and ectromelia virus (ECTV), where the encoded proteins are known as SPICE, MOPICE, CPV-IMP, and EMICE, respectively (16)(17)(18)(19).…”
mentioning
confidence: 99%